A bushfire monitoring and detection system for smart homes using ZigBee technology. (22nd December 2009) - Sun, Ying; Yuan, Quan; Al-Sarawi, Said
This paper describes the part of a smart monitoring system that uses ZigBee modules to communicate sensory information in case of a fire or bushfire. The proposed system is composed of two parts: A number of remote boards that collect temperature and humidity; and a host board that contains the same type of sensors as the remote board, in addition to wind speed and wind directions sensors. The proposed system can be used for monitoring and detection of both bushfire and fire in and around a house. The host board position and sensory information collected from the remote boards are combined, stored and processed by a microcontroller. The host board performs further processing on the collected sensory information and communicates it to a control room wirelessly using a long range wireless communication such as wireless local area network (WLAN) or general packet radio service (GPRS). The system components and performance are also described.